Improvement of Modern Methods of Treatment of Chronic Periodontitis - Normuradov Nodirjon Alisherovich (Zien Journals, 2023)
The article is of great theoretical and practical importance, written to improve and deepen students' knowledge. The article entitled "Improvement of modern methods of treatment of chronic periodontitis in therapeutic dentistry" includes all the achievements and innovations of today. It forms knowledge about the concept of the occurrence of periodontitis, the essence, characteristics and forms, methods of treatment, materials used. The relevance of the information given in the article, the planned methods of treatment using foreign literature and the results obtained after treatment have a clinical and statistical basis.
Keywords: periodontal disease; chronic; acute